Kontekstualisasi Soal Berbasis Numerasi pada Pembelajaran Matematika Sekolah Dasar di Kabupaten Lombok Barat - Haryadi, Herjan (Media Pendidikan Matematika, 2024)
Contextualization is a form of transformation process through various real problems in mathematical form. The context of the questions plays an important role as a stimulus to better understand numeracy in mathematics learning. Mathematical numeracy is the knowledge and skills used with various numbers and symbols to solve various problems in everyday life. The aim of this research is to analyze the contextualization of numeracy-based questions in fifth grade mathematics learning in elementary schools in West Lombok district. The research method used is a qualitative method with a multi-case study approach. The subjects used were students, teachers and school principals. The research techniques used are interviews, observation and documentation. The data analysis used is reduction, data display, drawing conclusions and data verification. The validity of the data uses extended observations, researcher persistence and triangulation. The results of the research were that in the personal context, case 1 the teacher never presented personal context questions directly or very rarely. Meanwhile, in case 2, there was no personal context at all in the question text. In the socio-cultural context, both case 1 and case 2 did not include this in the question paper. Lastly, in the scientific context of case 1, the question paper was included in the text, but it was still simple and not accompanied by pictures or infographics